PENGARUH MODEL PEMBELAJARAN RME (REALISTIC MATHEMATIC EDUCATION) TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI BANGUN RUANG - Rezkiani Junita, Maulida; Halim, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mathematics learning outcomes of fourth-grade students in SDN Kunciran 9. The purpose of this study is to determine the effect of the RME (Realistic Mathematic Education) learning model on the mathematics learning outcomes of fourth-grade students in class IV B. This study is aquantitative research with a pre-experimental type in the form of one group pretest posttest design. The population in this study consists of 64 students, which includes 33 students from class IV A and 31 students from class IV B. The sampling technique used is purposive sampling with a sample size of 33 students from class IV A. The data collection techniques used in this study are tests, questionnaires, and documentation. The results of this study show that the paired sample t-test produced a t-table value of 2.042 and a t-count of 10.112. Thus, t-count 10.112 > t-table 2.042. This proves that Ho is rejected and Ha is accepted, which means there is an influence of the Realistic Mathematic Education (RME) learning model on the mathematics learning outcomes of fourth-grade students.